Essays on Conceptual Electrochemistry: I. Bridging Open-Circuit Voltage of Electrochemical Cells and Charge Distribution at Electrode–Electrolyte Interfaces - Huang, Jun; Zhang, Yufan (Frontiers in Chemistry, 2022)
We discuss how an electrochemical cell conforms itself to the open circuit voltage (OCV) given by the Nernst equation, where properties of the electrodes play no role. We first show, via a pedagogical derivation of the Nernst equation, how electrode properties are cancelled, then take a closer look into the electrode-electrolyte interface at one electrode by linking charge and potential distributions. We obtain an equilibrium Poisson-Nernst equation that shows how the charge distribution across an electrode-electrolyte interface can be dictated by chemical potentials of redox species. Taking a H_2/O_2 fuel cell as an example, we demystify the formal analysis by showing how the two electrodes delicately regulate their “electron tails” to abide by the Nernst equation. In this example, we run into a seemingly counter-intuitive phenomenon that two electrodes of the same material display two distinct potentials of zero charge.